Rinodina mayrhoferii sp. nova new taxon for the spanish lichen flora. - Crespo, Ana M. (Lazaroa, 2014)
A new epiphytic lichen species of dxc genus Rinodina is described. Rinodina mayrhoferi Crespo has bicincta-type spores (POELT & MAYRUOFER, 1979), and grows usually on Juniperus ¡hurifera (lera L., always in continental localities of the Iberian Peninsula.